Smart Intelligent Computing and Applications Proceedings of the Third International Conference on Smart Computing and Informatics, Volume 1 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Mohanty, J. R.; Udgata, Siba K. (Smart Innovation, Systems and Technologies, 2020)
XX, 793 p. 366 illus., 266 illus. in color.